A low‐cost X‐ray‐transparent experimental cell for synchrotron‐based X‐ray microtomography studies under geological reservoir conditions. (1st January 2014) - Fusseis, Florian; Steeb, Holger; Xiao, Xianghui; Zhu, Wen‐lu; Butler, Ian B.; Elphick, Stephen; Mäder, Urs
<x xml:space="preserve">Abstract</x> A new modular X‐ray‐transparent experimental cell enables tomographic investigations of fluid rock interaction under natural reservoir conditions (confining pressure up to 20 MPa, pore fluid pressure up to 15 MPa, temperature ranging from 296 to 473 K). The portable cell can be used at synchrotron radiation sources that deliver a minimum X‐ray flux density of 109 photons mm−2 s−1 in the energy range 30–100 keV to acquire tomographic datasets in less than 60 s. It has been successfully used in three experiments at the bending‐magnet beamline 2BM at the Advanced Photon Source. The cell can be easily machined and assembled from off‐the‐shelf components at relatively low costs, and its modular design allows it to be adapted to a wide range of experiments and lower‐energy X‐ray sources.